19 Can heart failure ever be clinically stable? A report on the outlook of community-diagnosed heart failure patients managed in a disease management programme. (16th October 2019) - Redmond, A; Gallagher, R; O'Connell, E; Murphy, R; Healy, L; Barrett, M; Barrett, P; Halley, C; Ledwidge, M; McDonald, K
Abstract : Significant advances have been made in the management of heart failure (HF). However, the focus remains on the risk that patients remain exposed to in terms of shortened life expectancy, hospital admissions and increasing morbidity in the outpatient setting. In part, this focus reflects the fact that reports generally come from at-risk cohorts often identified at the time of, or near to a hospitalization for HF. Little is known on the natural history of patients diagnosed with HF in the outpatient setting and managed within a HF disease management programme (DMP), and in particular whether patients with HF in this setting can describe a benign clinically stable course. To address this we report on patients diagnosed with HF in the outpatient setting by a consultant cardiologist and followed in a DMP. Patients had complete work-up of cause, appropriate medical and device-based management and education in self-care. Follow-up was individualized as to clinical need but at a minimum included annual review to assess stability and need for treatment adjustment. For this report we included all patients who had at least one annual follow-up from the time of diagnosis or who had died during that first year. Clinical stability was defined as alive, free from any cardiovascular admission, no alteration in diuretic comparing the prescriptions at last follow up with second prescription from the HF unit and no increase in natriuretic peptide > 30% comparing latest value with baseline value. Logistic regression analysis was performed to look for predictors of clinical stability. Data are presented as mean with interquartile range. We report on a population of 509 patients (48% male, mean age 79.2 yrs). Mean follow up was 3.7 years. Clinical stability as defined above was observed in 184 patients, a substantial minority of the cohort (36%). This cohort were identified as being younger [77.7 (66–82) vs 79.6 (75–84 yrs), p=0.038), with no gender difference and similar prevelance of HF preserved and reduced ejection fraction. Independent predictor of clinical stability were younger age, lower presentation B-type NP [165 (75–325 pg/ml) vs 268 (141–468 pg/mg), p=0.001] and lower prevalence of atrial fibrillation (43 versus 51.4%). In summary, these data indicate that HF can be a stable syndrome with slightly more than a third of patients diagnosed in the community with subsequent management within a DMP demonstrating a benign clinical course over a follow-up period of almost four years. Optimal definition of this group might allow for their care to be managed more in primary care freeing up hospital services for management of the sicker cohorts.